Analisis Keputusan Musyawarah Nasional Lembaga Bahtsul Masail Nahdlatul Ulama Tahun 2019 Tentang Hukum Bisnis Multi Level Marketing - Latifah, Umi; Baihaqi, Yusuf; Jayusman, Jayusman (Universitas Islam Negeri Raden Intan Lampung, 2021)
One form of cooperation being developed today is a tiered direct selling system or often called Multi Level Marketing (MLM). Even though the MLM business is developing quite well in Indonesia, there are not a few incidents that show that people are disadvantaged and even deceived by this MLM business. Various legal interpretations emerged from several scholars, some declared it halal, some stated it was unlawful. In 2019 the social organization Nahdlatul Ulama (NU) at the National Conference of the Bahtsul Masail NU Institute also discussed MLM business law. This research is a qualitative research and includes a type of library research. The research approach method used is the juridical, historical, and uṣūl fiqh approach. The nature of this research is descriptive-analysis, which describes a situation or a subject, and then analyzes it. The results obtained from this study are: (1) MLM business law in an Islamic review based on the 2019 National Assembly of the NU Bahtsul Masail Institute is haram. This prohibition is intended for MLM types with sun, pyramid or ponzi schemes that contain money game practices or fraud. (2) MLM business law is analyzed using the theory of sadd aż-żarīʻah when viewed from the level of damage (mafsadatan) caused, MLM is a business that is basically permissible to do because it contains benefits, but allows harm to occur.Keywords: Multi Level Marketing, National Conference Bahtsul Masail NU, Sadd aż-Żarīʻah,